Inclined borehole and velocity measurement - Stojanović, Krešimir (Geologija, 1987)
In the paper the inclination of borehole and its influence on accuracy of velocity measurement and vertical seismic profiling are considered. Solutions are given for elimination of inaccuracies owing to deviations from verticality, as well as listing of computer programs for calculation of velocity measurements which take into account also inclination of borehole and various sources of signal. Shown are examples for three cases of velocity measurements in dependance of azimuth of source, of direction of depth standpoint with axis of vertical borehole as a reference, and of inclination of deep borehole.